A educação popular contribuindo na recriação dos espaços escolares nas escolas municipais do meio rural - Lipsch, Verenice Teresinha (2007)
The present research has as worry to investigate what necessity arises to popular education and what its contribution to educational policies since society is organized to formal education. The greatest objective is enable a discussion about popular education, in perspective of establishing processes able to recreate school educational space, having as basic principles militancy, participation and pedagogical praxis. We have based our research on authors of great relevance to the proposed theme, Hurtado, Mejia, Jiménez, Brandão, Freire, Paludo and the like. We have had as reference, activities at Centro de Educação Popular, in cities of Alto Uruguai region, from one of its acting axis on, which develops continued education of the educator and the implementation or democratic management process as essential policies for the joining of school education with popular education. To accomplish our investigation, we have used the praxis methodology as a way to concretize dialectic so that we could relate the conception of popular education that bases us with the work that is accomplished. We believe the possibility that the school education can be joined to popular education and the latter can contribute so that school spaces are recreated and pedagogical practice of the educator has a new meaning, since the implementation of a participating method, the opening of the school to the community, the accomplishment of a democratic work, a proposal of a continued education of educators, managers and teachers´ militancy, the use of a consultancy to contribute to the process leading and the political willing of leaders are guaranteed